Cebu's Basic Christian Community Movement's Alternative Plan for Sustainable Development - Nadeau, Kathy (Kasarinlan: Philippine Journal of Third World Studies; Vol 12 No 4 (1997): New Social Movements)
Based on selected indicators, Cebu has now recently become one of the most booming growth centers of the Philippines. However, these indicators are mere gauges of economic growth, not development. Development pertains to social and structural process for achieving ecological sustainability and human well-being within a community as a whole. In Cebu, there may have been an economic boom which favors selected few businessmen but, for most Cebuanos, there was none to speak of. Studies shoe that the so called “Ceboom” masks widespread environmental destruction caused by the real estate developers. The Medium-Term Cebu Development Plan (MTCDP) has neglected to develop basic social services and agriculture in order to alleviate poverty in the province. An alternative to this is the broader vision for sustainable development of the Basic Christian Community called Basic Ecclesiastical Community (BEC) movement. Involving a paradigm shift, BEC aims to develop a post capitalist society which is based on ecologically sustainable modes of production through the gradual reorganization of communities on the peripheries. Through their training programs and community organizing, the BEC movement in Cebu seeks to establish a self-sustaining economy based on local agriculture and supported by local industry. The author concluded that, although Cebu is in the forefront of development, the sustainable development can be attained by adopting the BEC’s model.
Keywords: Cebu, MTCDP, BEC